2000
DOI: 10.1051/agro:2000176
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of the Yr17 resistance to yellow rust of wheat in northern Europe

Abstract: International audienceThe gene Yr17, conferring resistance to Puccinia striiformis f.sp.tritici, was introduced into northern European wheat cultivars in the mid 1970s. Virulence for Yr17 was not detected until 1994, when it was identified in the UK and Denmark. In both countries, susceptible Yr17 cultivars were grown on an increasingly large area over the next four years and this was followed by a rise in the frequency of corresponding virulence to 100% . Elsewhere in northern Europe Yr17 cultivars were grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
133
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 2 publications
7
133
0
2
Order By: Relevance
“…Bayles et al (1) also reported that v17 isolates reached a frequency higher than 70% in 1999 in these countries. For each year and field, presence and proportions of pathotypes as defined by virulence genes were consistent with other regional surveys (1,7). We found that pathotypes 233E137V17 and 169E136V17 represented, respectively, 88.7 and 11.3% of the sampled isolates for years 1998 and 1999 ( AFLP reproducibility.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Bayles et al (1) also reported that v17 isolates reached a frequency higher than 70% in 1999 in these countries. For each year and field, presence and proportions of pathotypes as defined by virulence genes were consistent with other regional surveys (1,7). We found that pathotypes 233E137V17 and 169E136V17 represented, respectively, 88.7 and 11.3% of the sampled isolates for years 1998 and 1999 ( AFLP reproducibility.…”
Section: Discussionsupporting
confidence: 86%
“…In France, natural epidemics occur usually in the northwest and occasionally in the south and are especially damaging when springs are cool and rainy (6,7,38). In most cases, the use of specific resistance genes as a disease control method has been unsuccessful because the pathogen population evolves rapidly and is able to overcome a newly introduced resistance gene within only a few years (1,32,36). Other methods have been investigated, such as pathotypenonspecific resistance or cultivar mixtures (37), but more detailed data about the genetic structure of natural populations are needed to understand and predict their efficacy.…”
mentioning
confidence: 99%
“…Recently, YR has become a serious threat to wheat, causing 50-100 % yield losses due to the breakdown of existing resistance genes and gradual adaptation of new strains in warmer regions, particularly the Central and West Asia and North Africa (CWANA) region (ICARDA, 2011). The breakdown of the widely used race-specific genes (R-genes) Yr17 (Bayles et al, 2000;Wan et al, 2004;Chen 2007), Yr27 (Singh et al, 2004;Wan et al, 2004), Yr31 Rosewarne et al, 2012), and Lr24 (Park et al, 2002) has created a serious challenge for wheat scientists and growers worldwide. Introducing genetic resistance into cultivars is the most economic and environmentally safe measure of rust disease management in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Both the resistance and virulence are inherited as single genes (Pedley and Martin, 2003). There are many recorded examples of directional selection leading to invasion of pathogen populations by virulent isolates, and hence resistance breakdown (Jacobs and Parlevliet, 1993;Bayles et al, 2000). However, there are some cases demonstrating that single R gene can conifer highly durable resistance (Kolmer, 1993;Parisi et al, 1993).…”
mentioning
confidence: 99%